The Effectiveness of Sunscreen Cream with Ethanol Extract of Sungkai Leaves (Peronema canescens Jack) - Budiati, Anarisa; Aulena, Desi Nadya; Khirana, Roro Dyah Ayu Chandra; Fitriyani, Dwi (Faculty of Pharmacy Universitas Pancasila, 2024)
Sungkai (Peronema canescens Jack) (PCL) contains flavonoid compounds that can absorb UV light therefore having the potential to be developed as a raw material for cosmetics that functions as a sunscreen. The research aims to formulate PCL extract into a sunscreen cream. Sungkai leaves are macerated using 96% ethanol solvent. Specific and non-specific parameter tests were carried out on the extract as well as antioxidant tests using the DPPH method and SPF tests using the Mansur method. The results of this research showed that 96% ethanol extract of PCL had a blackish-green color, pH 5.25; the ethanol and water-soluble essence levels were 6.25% and 5.17%. The water content obtained is 27.4%; drying shrinkage is 0.46%; total ash content is 0.12% and acid insoluble ash content is 0.1%. The antioxidant value obtained was 35.06 ppm. Three cream formulations were prepared (FI of 0.1753%, FII of 0.3506%, and FIII of 0.5259%) and evaluated for organoleptic, homogeneity, cream type, viscosity, pH, particle size, and spreadability tests for one month at 25℃ and 40℃. The organoleptic test results of the cream have a soft texture, with varying colors; light green (FI), green (FII), and dark green (FIII) color. Other evaluation test results show that the cream has a pH of 5.16 - 6.73, a spreadability of 6.47 - 8.07 cm, a viscosity of 15466.67 - 38933.33 cPs, a particle size of 9.88 - 16.17 µm and an SPF of 17.68 (FI), 27.46 (FII), and 33.64 (FIII) with ultra protection on all three. PCL extract after being formulated into creams shows high SPF activity with F3 as the best formula. PCL extract can be formulated into a cream form that meets physical and chemical quality parameters.